Some unusual scenes in the tombs of the members of the modern state (1549-1069 BC) in ancient Egypt, on the western bank of Luxor - Falih, Dr. Alaa Radhi (Thi Qar Arts Journal, 2023)
The ancient Egyptian civilization expressed many noble human values, which were a vivid expression of the reality of life at all levels, whether public life, religious life, or funeral life in accordance with their spiritual and temporal perceptions. This expression was manifested through tomb scenes, especially with regard to The western mainland of the ancient city of Luxor, and in particular in the era of the New Kingdom, in addition to the natural scenes that were included in the walls of these tombs, there were some unfamiliar scenes that were not repeated very often.